2016
DOI: 10.1158/1078-0432.ccr-15-2290
|View full text |Cite
|
Sign up to set email alerts
|

Girdin (GIV) Expression as a Prognostic Marker of Recurrence in Mismatch Repair–Proficient Stage II Colon Cancer

Abstract: Purpose Prognostic markers that identify patients with stage II colon cancers (CC) who are at risk of recurrence are essential to personalize therapy. We evaluated the potential of GIV/Girdin as a predictor of recurrence risk in such patients. Experimental Design Expression of full-length GIV was evaluated by immunohistochemistry (IHC) using a newly developed monoclonal antibody together with a mismatch repair (MMR)-specific antibody panel in three stage II CC patient cohorts, ie. a training (n=192), test (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 46 publications
5
21
0
Order By: Relevance
“…To do this, we developed a scoring system by which the expression levels were evaluated by both intensity scores and proportion scores (Figure E). Statistical analysis of 76 cases of skin cancer showed that the expression level of Girdin was upregulated in most cases of squamous cell carcinoma of the skin (Figure F, Table ), suggesting a role of Girdin in cancer progression, as already shown for other types of cancer including breast, colon, and brain tumors . We also found that Girdin expression level correlated well with the differentiation of the cancer (Table ) and the expression of β‐ and α‐catenins as well as E‐cadherin (Table ), suggesting that Girdin synergizes with its partner proteins in the progression of skin cancer.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…To do this, we developed a scoring system by which the expression levels were evaluated by both intensity scores and proportion scores (Figure E). Statistical analysis of 76 cases of skin cancer showed that the expression level of Girdin was upregulated in most cases of squamous cell carcinoma of the skin (Figure F, Table ), suggesting a role of Girdin in cancer progression, as already shown for other types of cancer including breast, colon, and brain tumors . We also found that Girdin expression level correlated well with the differentiation of the cancer (Table ) and the expression of β‐ and α‐catenins as well as E‐cadherin (Table ), suggesting that Girdin synergizes with its partner proteins in the progression of skin cancer.…”
Section: Resultssupporting
confidence: 77%
“…We and others have previously shown that Girdin is expressed by multiple types of cancers, where its expression correlated with cancer progression . In this study, we showed a role of Girdin in the collective invasion of skin cancer cells, where it interacts with β‐catenin, a component of the E‐cadherin complex .…”
Section: Introductionsupporting
confidence: 61%
“…These conclusions are in keeping with prior observations that polarity defects precede the onset of tumorigenesis when the LKB1-AMPK pathway is inhibited (Hezel et al., 2008), fueling the speculation that polarity defects may be one of the major mechanisms for tumor initiation when the energy sensing pathway is dysregulated (Hezel and Bardeesy, 2008). Multiple studies on GIV have demonstrated its role as a bona fide metastasis-related protein across a variety of cancers, primarily via its ability to initiate and amplify tyrosine-based G protein signals (Aznar et al, 2016; Ghosh, 2016) and couple it to actin cytoskeletal remodeling at the leading edge of migrating cells predominantly via interactions mediated by its C terminus [reviewed in (Ghosh, 2015)]. This study is the first of its kind that reveals the protective role of GIV's N terminus.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that although multiple retrospective clinical trials have generally concluded that prolonged use of Metformin reduces the incidence of cancer, others have reported conflicting results, and several prospective clinical trials are underway to identify which target populations may specifically benefit from this drug [reviewed in (Kourelis and Siegel, 2012; Pryor and Cabreiro, 2015)]. Given the widespread long-term use of metformin as a prescription drug and its potential utility both in chemoprevention as well as chemotherapy, further studies are warranted to investigate if the GIV-expression status in tumors [e.g., its expression as a spliced isoform lacking the C terminus (Ghosh et al, 2010) or mutants that prevent phosphorylation by AMPK (current work), or its overexpression as full length (Ghosh et al, 2016)] may help identify which patients may benefit from the tumor suppressive actions of the Metformin.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to be a signal transducer that modulates multiple signaling pathways (6, 1016). Recently, girdin was reported to serve as a useful prognosticator adjunct to traditional staging strategies in colon cancer, and its high expression predicts a worse outcome in esophageal squamous cell carcinoma (1719). However, the clinical implication of girdin in breast cancer has been investigated in a few studies involving small cohorts of patients.…”
mentioning
confidence: 99%